Indices, perception and evidentiality: the case of Spanish por lo visto and its French equivalence apparemment - Anscombre, Jean-Claude (Thélème. Revista Complutense de Estudios Franceses, 2025)
The aim of this study is to analyze and discuss the functioning of Spanish discourse marker por lo visto from the point o view of evidentility and speaker’s commitment. In view of the problems encountered with the usual approaches, we propose a new model of explanation based upon the concept of index and its relation to the (de-)commitment of the speaker. The last part is devoted to compare por lo visto to its French equivalence apparemment as far as aspect is concerned.